2023
DOI: 10.1007/s00417-023-06054-9
|View full text |Cite
|
Sign up to set email alerts
|

An AI model to estimate visual acuity based solely on cross-sectional OCT imaging of various diseases

Abstract: Purpose To develop an artificial intelligence (AI) model for estimating best-corrected visual acuity (BCVA) using horizontal and vertical optical coherence tomography (OCT) scans of various retinal diseases and examine factors associated with its accuracy. Methods OCT images and associated BCVA measurements from 2,700 OCT images (accrued from 2004 to 2018 with an Atlantis, Triton; Topcon, Tokyo, Japan) of 756 eyes of 469 patients and their BCVA were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The parameters that were evaluated in previous studies, after conducting a literature review using Pubmed and Google Scholar with the key words "MH, AI and OCT", did not include IRF, SRF, ELM and EZ interruption, and HRF. Instead, they considered BCVA and hole dimensions to create a predictive model for postoperative anatomical and functional outcomes [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters that were evaluated in previous studies, after conducting a literature review using Pubmed and Google Scholar with the key words "MH, AI and OCT", did not include IRF, SRF, ELM and EZ interruption, and HRF. Instead, they considered BCVA and hole dimensions to create a predictive model for postoperative anatomical and functional outcomes [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the prediction of VA in patients with mCNV is scarcely found [ 27 ]. According to a recent study by Inoda et al [ 27 ], prediction of VA in mCNV was inferior to that in neovascular age-related macular degeneration (nAMD) or retinal vein occlusion, with their estimated and actual VA corresponding to an R 2 value of 0.36.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the prediction of VA in patients with mCNV is scarcely found [ 27 ]. According to a recent study by Inoda et al [ 27 ], prediction of VA in mCNV was inferior to that in neovascular age-related macular degeneration (nAMD) or retinal vein occlusion, with their estimated and actual VA corresponding to an R 2 value of 0.36. However, their study aimed to predict VA using cross-sectional OCT images at a single time point rather than predicting post-injection VA with preinjection OCT images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation